Casein core-polysaccharide shell nanocomplexes stable at pH 4.5 enabled by chelating and complexation properties of dextran sulfate. (June 2020) - Li, Nan; Zhong, Qixin
Abstract: Casein micelle dispersions are turbid and unstable around the isoelectric point at pH 4.6. In this study, dextran sulfate (DS) was used to form stable and translucent 2% w/v casein dispersions at pH 4.5 through chelating calcium in micelles and forming nanocomplexes. Contrasting with turbid dispersions with large particles after brief mixing, thorough mixing micellar casein with DS stock dispersions resulted in stable and translucent dispersions after acidification to pH 4.5. The chelating capacity of DS was further confirmed by measuring ionic calcium. The dispersion turbidity was further reduced by changing pH from neutral to 11.30 to dissociate casein micelles followed by complexing with DS during acidification to pH 4.5. The formation of casein-DS nanocomplexes stable at pH 4.5 was mainly contributed to the electrostatic binding between basic amino acids of caseins and sulfate groups of DS, even when the two biopolymers were overall anionic at pH 7.6. Graphical abstract: Image 1 Highlights: Stable and translucent casein-dextran sulfate dispersions at pH 4.5 were prepared. Zeta potential results suggest core-shell structures of nanocomplexes at pH 4.5. Dextran sulfate chelates calcium dissociating casein micelles at neutral pH. The pH-cycle treatment led to the smallest nanocomplexes and turbidity at pH 4.5. Electrostatic binding is the major mechanism forming nanocomplexes.